Validation of Sherlock, a linear trajectory analysis program for use in bloodstain pattern analysis. Issue 2 (3rd April 2019) - Orr, Amanda; Illes, Mike; Beland, Jacques; Stotesbury, Theresa
Abstract: This research validates the accuracy and efficacy of Sherlock, a recently developed program that estimates the area of origin (AO) of an impact pattern. Sherlock is an open-access, web-based software that conducts trajectory analysis by using the tangent method to estimate the area of origin. Fifty impact patterns were created at known X -, Y -, and Z -coordinates and were analyzed by upper year forensic science undergraduate students at Trent University. Individual stain data collected for each pattern were analyzed by both Sherlock and BackTrack TM /WIN. In this validation, we assess two objectives. The first evaluates the overall accuracy of the Sherlock program and the second compares the AO results between Sherlock and BackTrack TM /WIN when analyzing the same stain data. The average absolute deviation from the known using Sherlock was found to be 5.6 cm for the X -coordinate, 2.3 cm for the Y -coordinate, and 6.6 cm for the Z -coordinate. Further, when comparing the three-dimensional (3D) coordinate vector values, which considers all three coordinates as a single value, the Sherlock and known 3D AOs were shown to be similar with an average absolute deviation of 3.5 cm. Comparison between BackTrack TM /WIN and Sherlock provided statistically similar results for all comparisons ( p  > 0.05 in all cases), with average absolute deviations of 0.28 cm, 0.13 cm, and 0.75 cm in the X -, Y -, and Z -coordinates, respectively. This research demonstrates that the accuracy of the Sherlock program is comparable to a previously validated AO analysis program with similar absolute deviation from the true AO for single surface impact patterns.